RESEARCH CONTRIBUTIONS OF J.S. YADAV TO CHEMICAL SCIENCES: A SCIENTOMETRIC STUDY - Varaprasad, S.J.D.; Sahoo, Sidhartha; S., Madhusudhan (Malaysian Journal of Library and Information Science, 2010)
This paper highlights quantitatively the growth and development of chemical science research bym J.S.Yadav during the period from 1986-2009. During this period he has published 722 papers (702 research articles) in various domains. The data used was from Thomson/ISI Web of Science. This study attempts to evaluate the publications of J.S. Yadav in relation to his contribution to the knowledge domain of chemical science and his role for the advancement of chemical science in India and elsewhere in a span of about two and half decades. His papers have been scattered in 56 highimpact factor scientific journals. The percentage of collaborative work (99.7) was very high. His highest degree of collaboration 0.1925, was found during 2002-2003.The h index of 41 after 24 years of scientific activity is a clear indication of his consistent publication productivity behaviour